2021
DOI: 10.1108/hff-11-2020-0706
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body acceleration on the dispersion of solute in a non-Newtonian blood flow through an artery

Abstract: Purpose The purpose of this study is to solve convective diffusion equation analytically by considering appropriate boundary conditions and using the Taylor-Aris method to determine the solute concentration, the effective and relative axial diffusivities. Design/methodology/approach >An analysis has been conducted on how body acceleration affects the dispersion of a solute in blood flow, which is known as a Bingham fluid, within an artery. To solve the system of differential equations analytically while v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The Navier-Stokes and solid equations are given by Eqs. ( 3) and ( 4), respectively 17,43,48,82,83 . It should be noted that the first node of elements is defined as the reference point for software calculations [84][85][86] .…”
Section: Methodsmentioning
confidence: 99%
“…The Navier-Stokes and solid equations are given by Eqs. ( 3) and ( 4), respectively 17,43,48,82,83 . It should be noted that the first node of elements is defined as the reference point for software calculations [84][85][86] .…”
Section: Methodsmentioning
confidence: 99%
“…Blood was modelled with uniform density, r = 1060 kg/m 3 , and laminar flow conditions were assumed due to the low Reynolds numbersless than 1300 (Yamamoto et al, 2004) in the renal vasculature. Numerical studies have shown that factors including the non-Newtonian properties of blood and body accelerations can affect solute dispersion in blood flow (Saadun et al, 2021); non-Newtonian properties have also been shown to be essential when modelling targeted delivery of therapeutic agents (Tiam Kapen et al, 2022). Nonetheless, a constant viscosity of m = 0.00345 Pa•s, based on blood's lowest viscosity limit, was ascribed to the blood for three main reasons: it yields more exaggerated flow disturbances than non-Newtonian blood rheological models (Vijayaratnam et al, 2015); the wall shear stress thresholds used in the present study were originally obtained (Chen et al, 2015;LaDisa et al, 2004), and; the choice of blood rheological model has negligible impact on the drug transport behaviour in the context of stented arteries (Vijayaratnam et al, 2015(Vijayaratnam et al, , 2019.…”
Section: Hff 3212mentioning
confidence: 99%
“…After comprehensive peer review, only one third papers qualified for acceptance for final publication. This special issue comprises the theoretical and experimental research articles that elucidate the research efforts and recent developments on “New Trends in Heat and Fluid Flow: Applications and Recent Developments.” This issue consists of (Agrawal et al , 2021; Akbari et al , 2021; Alanazi et al , 2021; Alkanhal, 2021; Chang et al , 2021; Chen et al , 2021; Dehghan et al , 2021; Hayat et al , 2021; Riaz et al , 2021; Saadun et al , 2021; Safdari Shadloo, 2020; Selimefendigil and Öztop, 2021; Ullah et al , 2021; Xing et al , 2021; Yilmaz, 2021; Youjun et al , 2020; Zaher et al , 2021; Zhang et al , 2020) accepted papers related to fluid dynamics; heat exchangers; heat transfer enhancement; heat and mass transfer in thermal energy; heat and mass transfer in porous media; heat transfer phenomena in biological systems; nanofluids; two-phase/multiphase flows; Newtonian and non-Newtonian fluids; thermodynamics; and numerical simulations and methods. The presented results are discussed with an adequate physical interpretation.…”
Section: Special Issue On New Trends In Heat and Fluid Flow: Applicat...mentioning
confidence: 99%